The application of short and highly polymorphic microhaplotype loci in paternity testing and sibling testing of temperature-dependent degraded samples - Wen, Dan; Xing, Hao; Liu, Ying; Li, Jienan; Qu, Weifeng; He, Wei; Wang, Chudong; Xu, Ruyi; Liu, Yi; Jia, Hongtao; Zha, Lagabaiyila (Frontiers in Genetics, 2022)
Paternity testing and sibling testing become more complex and difficult when samples degrade. But the commonly used genetic markers (STR and SNP) cannot completely solve this problem due to some disadvantages. The novel genetic marker microhaplotype proposed by Kidd’s research group combines the advantages of STR and SNP and is expected to become a promising genetic marker for kinship testing in degraded samples. Therefore, in this study, we intended to select an appropriate number of highly polymorphic SNP-based microhaplotype loci, detect them by the next-generation sequencing technology, analyze their ability to detect degraded samples, calculate their forensic parameters based on the collected 96 unrelated individuals, and evaluate their effectiveness in paternity testing and sibling testing by simulating kinship relationship pairs, which were also compared to 15 STR loci. Finally, a short and highly polymorphic microhaplotype panel was developed, containing 36 highly polymorphic SNP-based microhaplotype loci with lengths smaller than 100 bp and Ae greater than 3.00, of which 29 microhaplotype loci could not reject the Hardy-Weinberg equilibrium and linkage equilibrium after the Bonferroni correction. The CPD and CPE of these 29 microhaplotype loci were 1-2.96E-26 and 1-5.50E-09, respectively. No allele dropout was observed in degraded samples incubated with 100°C hot water for 40min and 60min. According to the simulated kinship analysis, the effectiveness at the threshold of 4/-4 reached 98.39% for relationship parent-child vs unrelated individuals, and the effectiveness at the threshold of 2/-2 for relationship full-sibling vs unrelated individuals was 93.01%, which was greater than that of 15 STR loci (86.75% for relationship parent-child vs unrelated individuals and 81.73% for relationship full-sibling vs unrelated individuals). After combining our 29 microhaplotype loci with other 50 short and highly polymorphic microhaplotype loci, the effectiveness values at the threshold of 2/-2 were 82.42% and 90.89% for relationship half-sibling vs unrelated individuals and full-sibling vs half-sibling. The short and highly polymorphic microhaplotype panel we developed may be very useful for paternity testing and full sibling testing in degraded samples, and in combination with short and highly polymorphic microhaplotype loci reported by other researchers, may be helpful to analyze more distant kinship relationships.